VISUALIZATION OF FORECASTING NUMBER OF PATIENTS VISITING IN PRATAMA CLINIC USING ARIMA METHOD - Mardiani Trisno Putri (Penerbitan Universitas Trisakti, 2021)
The Primary Clinic of the Ministry of Communication and Information of the Republic of Indonesia had a problem that is difficulty in predicting the number of patient visits resulting in a buildup of patients in the clinic. For this reason, it is necessary to forecast patient visits in order to be the basis for planning for the next period and become a material consideration for decisions in clinical development. The research method was conducted using ARIMA by utilizing historical data on clinic visits from 2014-2019. The processed results in RStudio in the form of prediction data for patient visits in 2020-2021 are visualized on a website that uses the PHP Codeigniter framework and is integrated with RStudio. The results of visit forecasting based on services using the ARIMA method have good forecasting abilities, because the MAPE values are in the range of <10% and 10-20%, namely 19.58% and 9.62%.